Editorial: The role of medical physics in lung SBRT. (January 2018) - Mancosu, Pietro; Nisbet, Andrew; Jornet, Núria
Highlights: Medical physicists helped in the starting of SBRT for non-operable NSCLC patients. This special issue focused on physics challenges in lung SBRT. Physicists could lead the safe implementation of SBRT. Abstract: Stereotactic body radiation therapy (SBRT) has become a standard treatment for non-operable patients with early stage non-small cell lung cancer (NSCLC). In this context, medical physics community has largely helped in the starting and the growth of this technique. In fact, SBRT requires the convergence of many different features for delivering large doses in few fractions to small moving target in an heterogeneous medium. The special issue of last month, was focused on the different physics challenges in lung SBRT. Eleven reviews were presented, covering: imaging for treatment planning and for treatment assessment; dosimetry and planning optimization; treatment delivery possibilities; image guidance during delivery; radiobiology. The current cutting edge role of medical physics was reported. We aimed to give a complete overview of different aspects of lung SBRT that would be of interest to both physicists implementing this technique in their institutions and more experienced physicists that would be inspired to start research projects in areas that still need further developments. We also feel that the role that medical physicists have played in the development and safe implementation of SBRT, particularly in lung region, can be taken as an excellent example to be translated to other areas, not only in Radiation Oncology but also in other health sectors.